Fra valgstedet til indkøbscenteret: Danskernes stigende brug af brevstemmer - Bhatti, Yosef; Dahlgaard, Jens Olav; Hansen, Jonas Hedegaard; Hansen, Kasper Møller; Olsen, Mariann Malchau (Politik, 2016)
It is becoming increasingly popular among Danes to use early voting. The article describes the changes that have been made in the electoral law to accommodate the use of early voting and describes the historical development in the use of early voting. In addition, we show that there is considerable variation in the use of early voting at the municipal level, and that it is especially the citizens of the island municipalities, rich municipalities and metropolitan municipalities that use early voting. In the third part of the analysis, we examine individual differences in the use of early voting with the help of a data set with over two million Danish voters in the municipal elections in 2013. We show that early voting is primarily used by the oldest citizens and citizens with a non-technical education – two groups that traditionally have turned out at high rates. Finally, we analyze the characteristics that can help to predict which citizens use early voting.